Enhancing Students’ Chemical Representation Ability Through Problem-Based Learning Assisted by Nearpod on Electrolysis Cell Material - Nurida Siti Fatimah Zain; Cucu Zenab Subarkah; Yulia Sukmawardani; Sari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to show an increase in students’ chemical representation ability through the integration of Problem-Based Learning (PBL) assisted by Nearpod on electrolysis cell material and describe student activities and their ability to complete worksheets. This study used a pre-experimental method with a one group pretest-posttest design and involved second-semester students in the basic Chemistry 2 courses. The results showed that the improvement in chemical representation ability was in the medium category (N-Gain: 0.68), learning activities were carried out very good (88.86%), and the student’s ability to complete worksheets was also classified as high (average score: 89.52). These findings indicate that integrating PBL assisted by Nearpod is an effective, innovative approach to improving students’ chemical representation ability, particularly in abstract electrolysis cell material, by encouraging active participation and conceptual understanding.